Pelatihan Pembuatan Alat Peraga Replika Sel Hewan dan Sel Tumbuhan di SMPN 1 Wonomuyo - Dien Aulia Bansu; Ramlawati Ramlawati; Sitti Rahma Yunus (JKM: Jurnal Kemitraan Masyarakat, 2023)
Meaningful learning is the process of relating new information obtained and then linked to the structure of understanding that has been known in the learning process. Teachers need learning media that can support student understanding. Media is needed to visualize abstract material so that it can be more easily understood by students. Learning media that can be used in science learning are teaching aids. After making observations at SMP Negeri 1 Wonomulyo, it is known that the material of the life organization system is one of the materials that is difficult to understand because many use foreign terms such as organelle names and the size of microscopic cells make this material abstract. Service activities begin with observation of the needs of teaching aids to the evaluation and exhibition stages. Based on data analysis of evaluation instruments on simple science props made, it shows that animal cell replica props and plant cells can increase students' interest and understanding. The use of science props replicas of animal cells and plant cells is effective with a percentage of 78.4% and is in practical cateroggy, so it can be known that the teaching aids developed and used are able to measure competence in student learning.